How Cognitive Linguistics Affect Indonesian Students’ Understanding on Learning Phrasal Verbs - Gema Febriansyah; Syahrul Ramadhan; Mukhaiyar (Jurnal Arbitrer, 2023)
Phrasal verb is one aspect of English that is often avoided by EFL learners, including students in Indonesia. This is usually due to the method of learning phrasal verbs that tends to make it difficult for learners. Hence, this research tries to present how cognitive linguistics affects Indonesian students’ understanding of learning phrasal verbs. This research takes about 50 students of Padang State Polytechnic, Indonesia as the research subject. The students were divided into two groups: those who learned phrasal verbs with the traditional method and those with the cognitive linguistics method. Each group of students was taught by different lecturers who used cognitive linguistics and traditional methods. Then, the students were tested on their understanding of phrasal verbs. This study employed a quasi-experimental causal-comparative research design; this research revealed that learning phrasal verbs with the cognitive linguistics method is able to produce a significant understanding of students’ ability to understand phrasal verbs. The results of the test found that students who learned phrasal verbs with the cognitive linguistics method had a score of 80 in understanding the meaning of phrasal verbs and a score of 76.8 in applying phrasal verbs in English sentences. While the test results of the traditional method group showed less good results. In-depth interviews, and questionnaires from this research show that cognitive linguistics method helps students in understanding the meaning of phrasal verbs although there are weaknesses in applying phrasal verbs into English sentences. The implication of this research finding is that cognitive linguistics method can be an effective approach for teaching phrasal verbs to EFL students.